The Effectiveness of the Total Physical Response Method in Teaching Vocabulary to Students at State Islamic Junior High School 4 Jakarta - Shofi Rifdah Aisy; Nawawi, Mukhshon; Albantani, Azkia Muharom (INTIFA: Journal of Education and Language, 2026)
In the context of the importance of Arabic language learning and its role in developing language skills and strengthening Islamic values, this study reveals that secondary-level students still face difficulties in mastering vocabulary due to the dominance of traditional teaching methods that focus on rote memorization without interactive activities. To address this issue, the study examines the effectiveness of the Total Physical Response (TPR) method, which integrates language with physical movement to make learning more active and meaningful. This research adopts a quantitative approach with a quasi-experimental design involving two groups: an experimental group taught using the TPR method and a control group taught using traditional methods, with a total sample of 54 students. Data were collected through pretests, posttests, and questionnaires, and then analyzed using normality and homogeneity tests, t-tests, SPSS software, and N-Gain calculations. The results indicate an increase in the experimental group’s mean score from 56 to 83, with a low N-Gain value (0.26), while the improvement in the control group was lower. The t-test results also demonstrate a significant difference supporting the effectiveness of the TPR method. In addition, the questionnaire results show a positive response rate of 96%, confirming that the implementation of the TPR method enhances students’ engagement and participation in Arabic vocabulary learning.